Simultaneous operation by the minilaparotomy approach in the presence of acute gangrenous calculous cholecystitis and hepatic hemangioma - A. V. Kapshitar (Zaporozhye State Medical University, 2013)
According to domestic surgeons the simultaneous operations (SO) in biliary surgery are carried out most often. Practical surgeons refer to performance of SO in the presence of acute cholecystitis (AC) reservedly enough. From all the patients with cholelithiasis SO are carried out in patients with AC in 6,9-30%. Postoperative complications are registered in 0,2-23,9% of patients, and lethal outcomes - in 2-20%. In structure of benign tumors of the liver hemangioma of the liver (LG) is found in 30-50% of patients. We didn't find messages about simultaneous excision of LG and a gall bladder in the patients with acute gangrenous calculous cholecystitis by the minilaparotomy approach. Research objective: to publish rare clinical observation - simultaneous excision of LG and a gall bladder by minilaparotomy approach in the patient with acute gangrenous calculous cholecystitis. Material and research methods The patient K., 55 years old was on treatment with the diagnosis of acute pneumonia? in the therapeutic department of the 4th city hospital from 13.03.12 till 17.03.12. Laboratory-biochemical data, radiography of the chest and abdominal cavities, re-ultrasounds were not very informative. CT: acute calculous cholecystitis. Liver abscess? Hepatic hemangioma S5. Only after third surgeon's consultation the patient was taken to the surgery department of CE City Clinical Hospital № 2 of Clinic of General Surgery of ZSMU 17.03.2013 at 15.00 with the diagnosis of acute calculous cholecystitis. Results of research After conservative preparation and control laboratory and biochemical researches, ultrasonography on 18.03.12 abdominal cavity was opened by right-hand transrectal vertical minilaparotomy approach at 10.50. Acute calculous cholecystitis was diagnosed. Dense perivesical infiltrate, gemangioma in the projection of S5 of the liver, 60х50 mm, of partially subcapsular location were found. Puncture of a gall bladder was carried out, pus was removed. Cholecystectomy from the neck with separate ligation of the cystic duct and the cystic artery, enucleation of liver hemangioma, hemostasis with electrocoagulation and 8-shaped catgut sutures were performed. Blood loss was 300 ml. Drainage of subhepatic area was performed. The wound was sutured in layers tightly. Histologic conclusion: acute gangrenous cholecystitis, cavernous liver hemangioma. Postoperative course was smooth. Drainages were removed from the abdominal cavity on the 5th day. Sutures were removed on the 12th day. He was discharged. Conclusions The described clinical observation shows possibility of performance of SO - enucleation of LG and cholecystectomy in the patient with acute gangrenous calculous cholecystitis by minilaparotomy approach on condition of LG localization near free edge of anterior segment of a liver. Small blood loss and operation lengthening without complications with all known positive sides of SO and minilaparotomy approach allow to recommend them in clinical practice.